2010
DOI: 10.1016/j.febslet.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and dynamics of mouse ARMET

Abstract: a b s t r a c tARMET is an endoplasmic reticulum (ER) stress-inducible protein that is required for maintaining cell viability under ER stress conditions. However, the exact molecular mechanisms by which ARMET protects cells are unknown. Here, we have analyzed the solution structure of ARMET. ARMET has an entirely a-helical structure, which is composed of two distinct domains. Positive charges are dispersed on the surfaces of both domains and across a linker structure. Trypsin digestion and 15 N relaxation exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Furthermore, MANF transcripts and protein levels are increased after ischemic and epileptic insults in the cerebral cortex, suggesting that MANF may have neuroprotective effects against neurotoxins and cerebral ischemia (Lindholm et al, 2008;Voutilainen et al, 2009;Yu et al, 2010). The crystal structure of mammalian MANF has revealed that the amino-terminal region of MANF family members contains a saposin-like domain which may interact with lipids and membranes whereas the carboxy-terminal region includes an intradomain cysteine bridge in a CXXC motif which may protect cells from endoplasmic reticulum stress induced apoptosis (Hellman et al, 2010;Hoseki et al, 2010;Parkash et al, 2009). MANF is also found in invertebrates; for instance, Drosophila MANF is expressed in glia and neurons, and knocking out manf expression leads to neuronal degeneration causing embryonic lethality, indicating that MANF is required for the maintenance of neural cells in the fly (Palgi et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, MANF transcripts and protein levels are increased after ischemic and epileptic insults in the cerebral cortex, suggesting that MANF may have neuroprotective effects against neurotoxins and cerebral ischemia (Lindholm et al, 2008;Voutilainen et al, 2009;Yu et al, 2010). The crystal structure of mammalian MANF has revealed that the amino-terminal region of MANF family members contains a saposin-like domain which may interact with lipids and membranes whereas the carboxy-terminal region includes an intradomain cysteine bridge in a CXXC motif which may protect cells from endoplasmic reticulum stress induced apoptosis (Hellman et al, 2010;Hoseki et al, 2010;Parkash et al, 2009). MANF is also found in invertebrates; for instance, Drosophila MANF is expressed in glia and neurons, and knocking out manf expression leads to neuronal degeneration causing embryonic lethality, indicating that MANF is required for the maintenance of neural cells in the fly (Palgi et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Human MANF shares 59% amino acid identity with CDNF. The study on MANF solution structure revealed that MANF is composed of two domains, a saposin-like N-terminal domain and a well-conserved flexible C-terminal domain with a cysteine bridge [6,7]. The cysteine bridge may be involved in catalyzing the formation of intramolecular disulfide bonds and protein folding in the endoplasmic reticulum (ER) because of its similarity to the active site motif of thiol/disulfide oxidoreductases [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the C-terminal domain is homologous to the SAP (SAF-A/B, Acinus, and PIAS) domain of Ku70 (C-Ku70), a well known inhibitor of proapoptotic Bax (13). During preparation of this article, Hoseki and co-workers (14) have independently determined the NMR structure of MANF (Protein Data Bank code 2RQY). Although the three-dimensional structure is highly similar to our solution structure with an r.m.s.d.…”
mentioning
confidence: 99%